Psilocybin: From Serendipity to Credibility? - Rucker, James J.; Young, Allan H. (Frontiers in Psychiatry, 2021)
Psilocybin has a long history of non-medical use and some infer from this that it has therapeutic utility. Early phase clinical trials with psilocybin suggest larger multicentre trials are required. These are ongoing but will take many years to complete. Meanwhile, retreat centres offering paid experiences with psilocybin truffles have been created, often using early phase clinical trial data as the basis for bold, public facing claims. This is unwise. The results from early phase trials cannot be generalised outside the settings they were undertaken in. To do so is misleading. Providing an unregulated drug intervention as a paid service contravenes the ethical principles of internationally agreed declarations and guidelines on human research that were laid down after the 1947 Nuremberg Trials and the 1962 Kefauver Harris Amendments. By ‘jumping the gun’, retreat centres may be undermining the very process that might justify their actions. This could repeat the mistakes of history.